Using Integra® Dermal Regeneration Template in Electrical Burn Injury Defect Reconstruction – a Case Report - Jović, Marko; Suđecki, Branko; Ćertić, Biljana; Isaković Subotić, Jelena; Jurišić, Milana; Marinković, Milana; Jovanović, Milan; Stojičić, Milan; Jeremić, Jelena (Medical Research, 2024)
Introduction: Electrical burn injuries present a major public health issue in industrialized countries, and unlike electrical arc flash burns often result in deeper and more extensive injuries, especially in hands and feet.  When choosing from the range of reconstructive modalities, prompt coverage of exposed defects is imperative, offering patients a better functional and cosmetic outcome. Patient review: A 26-year-old male was admitted into our facility’s Burns Unit following a high-voltage electrical burn injuries sustained on the same day.  After several debridement sessions, the left foot was left with a 100 square centimeter dorsal surface defect with the involvement of ankle joint region. The defect was covered using Integra® Dermal Regeneration Template (IDRT) with a 100% success rate both with the template and later split-thickness skin graft (STSG) application. No perioperative complications were reported, with satisfactory cosmetic and functional results at the 6-month follow-up appointment. Conclusion: IDRT can be considered a good surgical choice for effective defect coverage with satisfactory results. Nevertheless, the final outcome and patient recovery also often depend on multitude of other factors, such as the defect size and the involvement of underlying structures.
Keywords: Electrical Burn Injuries; Foot Defect; Integra® Dermal Regeneration Template; Skin Graft